Collaborative reading in a “lecture-less” class of college students - Bethany Marie Cabantac-Lumabi (ELT Forum: Journal of English Language Teaching, 2024)
Young and adult Filipinos are mostly into reading according to the results of the 2017 Readership Survey. However, the reading interest of Filipinos does not follow relative results in their reading comprehension based on the low proficiency level of the Philippines in the Programme for International Student Assessment (PISA) both in 2018 and 2022. The reading habits and comprehension levels of young students are carried on to their higher education. Previous studies have shown that reading in tertiary education is usually done as an assignment and assessment in the classroom instead of as a means for class discussion and facilitation of learning. Thus, this mixed-method study was conducted to revive and normalize reading in a “lectureless” college classroom or with limited lectures from the faculty. Guided by collaborative strategic reading (CSR) – a reading strategy to improve students’ reading comprehension with the help of peers in a group, this mixed-method study assessed the college students’ reading through a pretest in the first semester and a posttest in the second semester after collaborative reading and limited lectures. The results posited progressive reading scores among college students with continuous use of collaborative reading and facilitated learning of the college faculty. According to the college students, the FGD and class observation described the advantages of collaborative reading in a “lecture-less” class.  This study implies the progressive effect of reading and collaboration on students’ learning and college faculty’s facilitation of their learning instead of lecturing.